Feed the Future Bangladesh 2015: Zone of Influence interim assessment report - Ahmed, Akhter (International Food Policy Research Institute, 2018)
This document reports the results of the first interim assessment of Feed the Future’s population-based indicators for the ZOI in Bangladesh.